Profile of The Use Of Biquanide And Sulfonylurea Combination Drugs In Patients With Type 2 Diabetes Mellitus - Isnawati, Nafisah (The SDGS Forum Communication, 2024)
Diabetes mellitus (DM) was disease caused by a disorder of the pancreas where the insulin produced cannot be used properly by the body. This study aimed to determine the profile of the use of a combination of biguanid and sulvonylurea in patinet with type 2 diabets mellitus. this research was non experimental research with retrospective data colleteion methode and descriptive reasearhc design. the data source used is the patient's medical record data. the sample in this study was all type 2 diabetes mellitus patinet whoused combination biguanide and sukfonylurea drug at X jember hospital from October to November 2023 with a total of 50 patients. The sampling technique used the total sampling technique. The result showed that nearly half of the patient with type 2 diabetes mellitus were in the age range of 51-60 years by 20 (40%) and most of the patient were female, 32 (64%). the use of combination of biguanide an dsulfonylurea drugs, almost all patinet used a combination of metformin and glimepirid as many as 65(94,2%), for almost half the dose used metformin 500 mg and glimepirid 4 mg as many as 25 (36,2%) while the frequency of a small proportionused metformin 500 mg twice a day and glimepirid 4 mg once a day. type 2 diabetes mellitus patiens mostly suffer from the age range of 51-60 years and most of the patinet are female. The use of a combination of biquanid and sulfonyl urea drugs, most of the drugs used are metformin 500 mg twice a dat and glimepirid 4 mg once a day